NONLINEAR ANALYSIS OF FIBER-REINFORCED SELF-COMPACTING CONCRETE HOLLOW SHORT COLUMNS SUBJECTED TO CONCENTRIC AND ECCENTRIC LOADS - Ahmed Abd Ali Fahad; Prof. Dr. Nagham Tariq Hamad; Assist.Prof.Dr. Zainab Mohammed Ali Hussein (Journal Park Publishing, 2024)
This study examines the load capacity of fiber-reinforced self-compacting concrete hollow short columns under eccentric and concentric loads. Different opening sizes and longitudinal steel reinforcement are used for the columns. The finite element software ABAQUS was utilized to model and examine the columns. A verification analysis of the nonlinear finite element modeling is conducted using the experimental test result. The verification of the model is established by considering all specifications of the empirically tested columns in the modeling process. Upon comparing the modeling and test findings, it becomes evident that a strong concurrence exists between them. Consequently, the correctness of the modeling is demonstrated. Additionally, a parametric investigation conducted different longitudinal steel reinforcement ratios and opening sizes with the same modeling technique. The impact of these variables on the column load capacity is examined. It was found that increasing the hollowing ratio from 0% (solid) to 8.7% (opening size of 50 mm) to 19.6% (opening size of 75mm) reduced the ultimate Load by 11% and 19.56%, respectively. The increasing hollowing ratio causes an increase in axial displacement by 12.2% and 25.2% and lateral displacement by 9.9% and 28.6% in the same order mentioned above. The elevation of the longitudinal reinforcement ratio from 1% to 2% with different diameters of (8, 10, and 12) mm leads to an escalation in the ultimate Load by 7.39% and 8.47%, respectively. The elevation of the longitudinal reinforcement ratio from 1% to 1.53% causes an increase in axial displacement by 4.81% and axial displacement by 4.13%. In comparison, the elevation of the longitudinal reinforcement ratio from 1.53% to 2% causes an increase in lateral displacement by 5.0% and lateral displacement by 6.67%. 12. Finally, the numerical study conducted that when e/h increased (from 0 to 0.13 to 0.27 to 0.4), the models' ultimate Load, axial displacement, and lateral displacement decreased.
Keywords: Hollow Columns, Solid Columns, Steel reinforcement ratio, Opening Size, Nonlinear analysis, and Abaqus.